Solvent‐Assisted Lipid Bilayer Formation on Au Surfaces: Effect of Lipid Concentration on Solid‐Supported Membrane Formation. Issue 13 (6th January 2021) - Neupane, Shova; Betlem, Kai; Renner, Frank Uwe; Losada-Pérez, Patricia
Abstract : Solvent‐assisted lipid bilayer (SALB) formation is emerged as a versatile approach in forming supported lipid membranes (SLBs) on metal surfaces, interesting platforms for transducing a biological signal to an electrical readout where vesicle rupture is not straightforward. Herein, the effect of the lipid concentration in the organic solvent, a key parameter controlling SALB, is addressed in the low and high concentration limits of 1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine lipid on a Au surface. Quartz crystal microbalance with dissipation (QCM‐D) responses are correlated with atomic force microscopy (AFM) topographic and nanomechanical measurements. Upon SALB completion at both concentrations, QCM‐D and AFM topographical characterization suggest the formation of thin, although incomplete, lipid layers at the Au–liquid interface, with frequency and dissipation plateau values departing from well‐established homogeneous SLB responses. Nanomechanical analysis reveals the presence of mostly monolayers at low concentration due to lack of lipid material, while at high concentration excess of lipid material leads to the coexistence of diverse structures. Their formation stems from the SALB formation mechanism, based on lyotropic transformations upon solvent exchange, which differs from customarily vesicle rupture. Such mechanism leads to peculiar two‐step features in approach force curves on SLBs pointing toward a decoupling in bilayer leaflets when supported. Abstract : Combined gravimetric and nanomechanical analysis reveals clear differences in the formation of supported lipid membranes by solvent exchange at low and high lipid concentration in the organic solvent. Low lipid concentration yields mostly monolayers at the Au–liquid interface, while at high concentration lipid bilayers and multilayers coexist.